The Use of Guessing Game in Improving the Speaking Skills of Elementary School Students - Fitria Ayu Meiningsih; Suwarsih Madya (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2021)
ABSTRACTGuessing game is a part of Communicative Language Teaching (CLT), which will create an atmosphere for students to increase the desire to learn languages. However, learning with games makes students undisciplined and requires a long time. This study aims to determine the effect of learning English using a guessing game method on the speaking skills of elementary school students. The study is a one-group pretest-posttest design implemented at the Islamic Elementary School in Yogyakarta. The study sample consisted of 68 students in grade 6 in 2019. The sampling technique used was total sampling. The measured learning outcomes are speaking skills in pronunciation, vocabulary, grammar, fluency, and understanding. The data were processed using the Wilcoxon test. The results showed that the students' speaking skills improved after learning with guessing games. The speaking skills that improved significantly are pronunciation, vocabulary, and fluency. Grammar and comprehension, on the other hand, improved but not significantly. The conclusion is that the guessing game can improve the students' speaking skills even though it has not covered all of its aspects.ABSTRAKGame menebak merupakan bagian dari Communicative Language Teaching (CLT) yang akan menciptakan suasana bagi siswa dalam meningkatkan keinginan untuk belajar bahasa. Namun pembelajaran dengan permainan membuat siswa tidak disiplin dan membutuhkan waktu yang lama. Penelitian ini bertujuan untuk mengetahui pengaruh pembelajaran bahasa Inggris menggunakan metode menebak terhadap keterampilan berbicara siswa sekolah dasar. Penelitian ini merupakan penelitian dengan menggunakan desain satu grup dengan pre tes dan pasca tes yang dilaksanakan di Madrasah Ibtidaiyah Yogyakarta. Sampel penelitian berjumlah 68 siswa kelas 6 tahun 2019. Teknik pengambilan sampel yang digunakan adalah total sampling. Hasil belajar yang diukur adalah keterampilan berbicara berupa pengucapan, kosakata, tata bahasa, kefasihan, dan pemahaman. Data diolah menggunakan uji Wilcoxon. Hasil penelitian menunjukkan bahwa keterampilan berbicara siswa meningkat setelah melalui proses pembelajaran dengan permainan tebak-tebakan. Keterampilan berbicara meningkat secara signifikan adalah pengucapan, kosa kata dan kefasihan. Tata bahasa dan pemahaman meningkat tetapi tidak signifikan. Kesimpulannya adalah bahwa permainan tebak-tebakan dapat meningkatkan keterampilan berbicara siswa meskipun belum mencakup semua aspeknya.